2022
DOI: 10.1038/s41598-022-21365-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced terrestrial Fe(II) mobilization identified through a novel mechanism of microbially driven cave formation in Fe(III)-rich rocks

Abstract: Most cave formation requires mass separation from a host rock in a process that operates outward from permeable pathways to create the cave void. Given the poor solubility of Fe(III) phases, such processes are insufficient to account for the significant iron formation caves (IFCs) seen in Brazilian banded iron formations (BIF) and associated rock. In this study we demonstrate that microbially-mediated reductive Fe(III) dissolution is solubilizing the poorly soluble Fe(III) phases to soluble Fe(II) in the anoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…This was supported by the identification of active FeRM within the caves [4,14] and the presence of a Fe(III)depleted material (termed sub muros) behind the IFC walls [14]. Sub muros was found behind an Fe(III)-(hydr)oxide crust, which forms as a result of oxidation of the outermost exposed Fe(II) in the sub muros and the precipitation of Fe(III)-(hydr)oxide phases to form the crust [14]. This Fe(III)-(hydr)oxide crust is thought to create an O 2 barrier, limiting O 2 intrusion into the sub muros and allowing Fe(III) reduction to proceed, with the resulting Fe(II) being removed via groundwater.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…This was supported by the identification of active FeRM within the caves [4,14] and the presence of a Fe(III)depleted material (termed sub muros) behind the IFC walls [14]. Sub muros was found behind an Fe(III)-(hydr)oxide crust, which forms as a result of oxidation of the outermost exposed Fe(II) in the sub muros and the precipitation of Fe(III)-(hydr)oxide phases to form the crust [14]. This Fe(III)-(hydr)oxide crust is thought to create an O 2 barrier, limiting O 2 intrusion into the sub muros and allowing Fe(III) reduction to proceed, with the resulting Fe(II) being removed via groundwater.…”
Section: Introductionmentioning
confidence: 63%
“…Recent evidence has demonstrated that Fe(III)-reducing microorganisms (FeRMs) may be responsible for the reduction in poorly soluble Fe(III)-oxides in the host rock to Fe(II), supported by organic carbon from the terrestrial surface [4,[8][9][10][11][12][13][14]. This was supported by the identification of active FeRM within the caves [4,14] and the presence of a Fe(III)depleted material (termed sub muros) behind the IFC walls [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into cave microbiota has proven vital for the exploration of underground biodiversity, however current knowledge about the distribution of the diversity of microorganisms and their functionalities in natural cave environments in Brazil is incipient, especially regarding ferruginous caves (PARKER et al, 2022).…”
Section: Introductionmentioning
confidence: 99%